Students’ Learning Obstacles in Understanding Green Chemistry Within the Context of Soap-Making Process - Desrika Putri; Asep Supriatna; Hernani (Postgraduate, University of Mataram, 2025)
This study aims to investigate students’ learning obstacles in understanding Green Chemistry within the context of a soap-making activity. As sustainability becomes an increasingly important issue in science education, it is essential to understand how students engage with environmentally oriented chemistry concepts. This study employs qualitative case study approach. The participants consisted of five grade XI students (second-year high school), comprising two boys and three girls. The interviews were conducted at a private school in Bandung. Data were collected through semi-structured interviews with five main questions. The responses were analyzed using thematic analysis to identify key themes related to students’ learning challenges in understanding green chemistry, which were categorized into five main themes. The findings reveal that students face significant challenges in understanding Green Chemistry, particularly due to abstract concepts, limited classroom engagement, and teacher-centered instruction. Moreover, students often struggle to connect the theoretical principles of Green Chemistry with real-life applications, such as waste reduction or the use of renewable materials in everyday chemical processes. These findings highlight the importance of designing more interactive, context-based, and student-centered learning strategies. It is expected that the results of this study can serve as a foundation for developing instructional designs that better support students’ understanding of sustainability-oriented chemistry.